Status of Nitrogen in Different Parts of Cupuassu Tree in Oriental Amazon - Silva, Diocléa Almeida Seabra; Viégas, Ismael de Jesus Matos; Alves, osé Darlon Nascimento; Conceição, Heráclito Eugênio Oliveira da; Filho, Michel Sauma; Oliveira, Thiago Caio Moura (Journal of Agricultural Studies, 2022)
Despite the socio-economic importance of the cupuassu tree for the Amazon region, a few studies have aimed to evaluate the nutritional status of nitrogen in cupuassu plantations, especially in the different vegetative parts. Thus, this research aimed to quantify the content and accumulation of nitrogen in vegetative parts of two progenies of cupuassu trees in the Amazon region. The experiment was carried out in an area of intercropping cupuassu tree x açai palm x banana, at Embrapa Amazônia Oriental, located in Belém, in the state of Pará from 2003 to 2007. The experimental design adopted was completely randomized in a 2 x 4 x 4 factorial scheme with two progenies (PMI 186 (Codajás) and a PMI 215 (Manacapuru)) x four years of evaluation and four plant components (leaves, stems, primary branches and secondary branches) with five replications, in which each experimental unit was composed of a plant from each progeny. The two PMI(s) present nitrogen storage in the secondary branches, but the PMI 186 presented higher N accumulation than the PMI 215. N content was higher in the leaves in both progenies independent of the plant age, with values over 50% of the total content. Therefore, Cupuassu tree progenies under intercropping showed satisfactory N accumulations throughout the study. It can be concluded that it is being viable options in intercropping in agroforestry systems.